A, ENTREPRENEURSHIP: BUILDING THE LOCAL ECONOMY AND DIRECTING A COMPETITIVE FUTURE AMID THE 271T TIN CORRUPTION CASE BANGKA BELITUNG: KEWIRAUSAHAAN: MEMBANGUN EKONOMI LOKAL DAN MENGARAHKAN MASA DEPAN BERDAYA SAING DITENGAH KASUS KORUPSI TIMAH 271T BANGKA BELITUNG - Tiara, Tiara Augus Fitriani; Suci Wulandari; Indah Noviyanti (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
The Bangka Belitung Islands are known to be rich in tin resources so it cannot be deniedthat most of the people make their living from tin but are now shackled by the 271T corruption case.This study aims to evaluate how big the impact of entrepreneurship is on Bangka Island, especiallyCentral Bangka Regency, after the rise in tin corruption cases which disrupted people's work, apartfrom that local fishermen were also affected by the existence of sea mines. Entrepreneurship playsan important role in building local economies and guiding a competitive future. This research aimsto analyze how the Timah 271T Bangka Belitung corporation can increase its competitivecapabilities through entrepreneurship that is oriented towards developing local resources andincreasing community participation in the economic development process.This research applies a quantitative approach in its methodology and utilizes aquestionnaire as a data collection tool. The population studied was MSME entrepreneurs in CentralBangka Regency, with a total of 39 respondents. The multiple regression analysis used, namelySPSS version 27 software, was used as a data analysis method. The test results show that thecoefficient of determination is 0.288, which means that around 28.8% of the variation in thedependent variable can be seen in the independent variables studied. This value shows that the LocalEconomy and Competitiveness variables influence Entrepreneurship in MSMEs in Central Bangkaby 28.8%. The t test results show that Local Economy (X1) has no influence on Entrepreneurship,while Competitiveness (X2) has a significant influence on MSME entrepreneurship in CentralBangka. The results of this research will contribute to the development of effective entrepreneurialstrategies to increase the competitiveness of MSME entrepreneurs in Central Bangka and encouragelocal economic growth.